2021
DOI: 10.3390/ijms222413219
|View full text |Cite
|
Sign up to set email alerts
|

The New Therapeutic Approaches in the Treatment of Non-Alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most prevalent chronic liver disease which is characterized by extremely complex pathogenetic mechanisms and multifactorial etiology. Some of the many pathophysiological mechanisms involved in the development of NAFLD include oxidative stress, impaired mitochondrial metabolism, inflammation, gut microbiota, and interaction between the brain-liver-axis and the regulation of hepatic lipid metabolism. The new therapeutic approaches in the treatment of NAFLD are tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 123 publications
0
27
0
10
Order By: Relevance
“…As a typical overnutrition-derived disease, the prevalence of NAFLD was nearly 30% worldwide in 2019 [ 5 ]. Nevertheless, no specific drug for NAFLD has been approved by the FDA yet [ 35 ]. In our study, HFHFD completely induced hepatic steatosis, as shown by the pathophysiological observations and lipid staining of the liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…As a typical overnutrition-derived disease, the prevalence of NAFLD was nearly 30% worldwide in 2019 [ 5 ]. Nevertheless, no specific drug for NAFLD has been approved by the FDA yet [ 35 ]. In our study, HFHFD completely induced hepatic steatosis, as shown by the pathophysiological observations and lipid staining of the liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…87 Vice versa, the high prevalence of MAFLD in those DM, dyslipidemia, IR, hypertriglyceridemia, and obesity populations is also noted. 108,109 One meta-analysis tried to summarize the prevalence of MAFLD in DM population and found among 49 419 DM patients (mean age: 58.5 years; mean BMI: 27.9 kg/ m 2 ; males: 52.9%), the prevalence of MAFLD was 55.5% (95% CI, 47.3-63.7), and it was apparent in Europe (68.0%; 95% CI, 62.1%-73.0%). 109 Besides strong association between DM and MAFLD, DM patients are at higher risk to have much severe FLD.…”
Section: Diabetes Mellitus and Metabolic Dysfunction-associated Fatty...mentioning
confidence: 99%
“…Globally, it is estimated that 25% to 30% of the general adult population may have MAFLD, and 3% to 6% may have MASH. 106 MAFLD is a reflective of hepatic manifestation of the MeS or a spectrum of metabolic dysfunction, 65 which contains hyperglycemia, IR, dyslipidemia, hypertriglyceridemia, and obesity, 65,106,108 and it is further supported by those patients with MAFLD have high rates of MeS (43%), hyperlipidemia (69%), obesity (51%), and DM (23%). 84 Furthermore, the exacerbation or severe forms of FLD are apparently accompanied with metabolic dysfunction, and it is reported that up to 81% of MASH patients were obese.…”
Section: Diabetes Mellitus and Metabolic Dysfunction-associated Fatty...mentioning
confidence: 99%
See 1 more Smart Citation
“…With new data rapidly emerging on the complex pathogenesis of NASH, new therapeutic approaches are being developed, focusing on hepatic steatosis, inflammation, and fibrosis. Innovative therapeutic approaches in the treatment of NAFLD/NASH target molecules involved in its pathophysiological pathway, including PPARs agonists, glucagon-like peptide-1 (GLP-1) agonists, sodium/glucose transport protein 2 (SGLT2) inhibitors, farnesoid X receptor (FXR) agonists, probiotics, and symbiotics, as reviewed by Filipovic et al [ 11 ]. In addition, integrins have been proposed as new therapeutic targets for hepatic fibrosis.…”
mentioning
confidence: 99%